INKLUSIFITAS PENGARUSTAMAAN LITERASI DIGITAL PERSPEKTIF PENDIDIKAN PANCASILA - Mukhlishi, Mukhlishi; Fadli, Moh (Journal of Education Partner, 2024)
The younger generation will continue to grow up with unlimited access to digital technology and have different thinking patterns from previous generations. If it is not balanced with knowledge, it will easily become an instant generation. Digital literacy is needed in this situation to search, find, classify and understand accurate and relevant information. One of the difficulties of the digital literacy era is negative content. For example, material related to various issues and concerns related to SARA, which often triggers various horizontal conflicts between citizens or communities and various issues both on a local and global scale. Digital literacy must go hand in hand with individual capacity to access the internet, especially information and communication technology, so that everyone can understand it completely and there is no gap in understanding due to only obtaining one-sided information. Digital literacy plays an important role in improving students' skills in this digital era. . This really allows generations already at various levels of education to gain the skills and knowledge they need to be successful in the world of education and their future.